Advanced nitrogen removal from wastewater by combining anammox with partial denitrification. (March 2015) - Du, Rui; Peng, Yongzhen; Cao, Shenbin; Wang, Shuying; Wu, Chengcheng
Graphical abstract: Highlights: A novel process combining anammox with partial denitrification was established. The excess NO3 − -N was efficiently converted to NO2 − -N via partial denitrification. The maximum NRE of 94.06% was achieved with effluent TN under the limiting value. The process had potential in treatment for both high and low strength wastewater. Abstract: The anammox (anaerobic ammonium oxidation) process has attracted much attention for its cost-saving. However, excess nitrate is usually produced which should be further treated. In this study, an innovative process combined anammox with partial denitrification (nitrate → nitrite) was proposed for advanced nitrogen removal in two sequencing batch reactors (SBRs). The nitrate produced in anammox-SBR (ASBR) was fed into partial denitrification-SBR (DSBR), in which the nitrate was reduced to nitrite, and then removed by backflow of the nitrite to ASBR for secondary anammox process. Results showed that ∼80% nitrate in the effluent of previous anammox was converted to nitrite in DSBR. And the maximum nitrogen removal efficiency (NRE) of 94.06% was obtained with total nitrogen (TN) in the effluent of 10.98 mg/L in average. It indicated that desired effluent quality could be achieved, and the advanced nitrogen removal performance was attributed to the successful achievement of partial denitrification.